Cardiac Rhabdomyomas Associated with Tuberous Sclerosis Complex in 11 Children: Presentation to Outcome. (14th February 2013) - Kocabaş, Abdullah; Ekici, Filiz; Çetin, İbrahim İlker; Emir, Suna; Demir, Hacı Ahmet; Arı, Mehmet Emre; Değerliyurt, Aydan; Güven, Alev
<x xml:space="preserve">Abstract</x> Cardiac rhabdomyomas (CRs) are the most common heart tumors in children and closely associated with tuberous sclerosis complex (TSC). This study was performed to assess the presentation type, clinical course, treatment modalities, and outcome of the patients with rhabdomyoma, associated with TSC. We reviewed our patients with cardiac rhabdomyomas (CRs), who had received a diagnosis of TSC previously or during the follow-up period between June 1996 and January 2012, retrospectively. Thirty-two patients with TSC were evaluated and among them 11 patients (34%) were associated with CRs. Five patients (45%) had multiple tumors and consequently a total of 29 CRs were analyzed in our study. The median follow-up period was 2 years (range: 1 week–15 years). Clinical presentation was cardiac murmur in three patients, cyanosis in two patients and arrhythmia in one patient. Five patients were asymptomatic at the diagnosis and CRs were detected during routine cardiac evaluation for TSC. Cardiac tumors were diagnosed prenatally in two patients. Spontaneous regression rate was 31% and we experienced a complete regression of a tumor with an echogenic bordered tissue defect and septal thinning in a patient. Three patients had hemodynamically significant tumor obstruction; two of them underwent surgery. The other patient, who had multiple CRs, was treated medically with everolimus because of high-risk potential of surgery. Although surgical resection is the preferred treatment in most of the patients with hemodynamic instability, we need novel alternative medical therapies in some critically ill patients who cannot be operated due to various reasons.